Measuring the performance of urban management on the quality of life of informal settlements in Miandoab City - farhad Judi; rahim Sarwar; Sayeda Sediqeh Hasani Mehr (تحقیقات کاربردی علوم جغرافیایی)
The effectiveness of urban management plays a crucial role in the sustainable development of cities from various perspectives. A significant and influential dimension of urban management is the quality of life experienced by citizens across different neighborhoods. The enhancement of quality of life through management performance can be achieved via citizen participation, service provision, and transparency, among other factors. Consequently, this study aims to assess the impact of urban management performance on the quality of life in informal settlements within Miandoab City. The research employed a descriptive-analytical methodology, utilizing field data collected through a structured questionnaire. The validity of the questionnaire was established, and its reliability was determined using Cronbach's alpha, which yielded a value greater than 0.79. The study's statistical population encompassed 11,545 residents living in 10 informal settlements in Miandoab City. Utilizing Cochran's formula, a sample size of 313 was determined. The results indicated that the urban management index was statistically significant, with a p-value of 0.000, which is less than the threshold of 0.05. The average difference was calculated at -1.403, and the T-statistic was -54.8568, confirming that the urban management index for informal settlements in Miandoab is deficient. Furthermore, the regression model demonstrated that the urban management index, comprising five variables, has a coefficient of 0.901, indicating a 90% efficacy in enhancing the quality of life in informal settlements.  Among the variables, the participation variable, with a coefficient of 0.231, accounted for 23% of the variation in the quality of life in neighborhoods. The urban facilities and infrastructure variable predicted 21% of the quality of life, while the financing, provision of municipal services, and environmental cleanliness and hygiene variables contributed 16%, 18%, and 11%, respectively, to the improvement of quality of life in informal neighborhoods.